The returns to skill and racial difference in parenting: Evidence from the civil rights movement - Owen Thompson (University of Massachusetts, Department of Economics, 2011)
On average, the parental practices adopted by African American parents of young children are much less cognitively stimulating than those of their white counterparts. This paper argues that these differences stem from the low rates of return to human capital historically experienced by African Americans. To study the relationship between the race-specific returns to skill and parenting, I use intergenerational data containing direct measures of parental behaviors, and examine the child rearing practices of mothers who came of age in the wake of the Civil Rights Movement, during a period of rapidly increasing returns to skill for African Americans in the US South. I find that among Southern African American mothers born between 1957 and 1964, each yearly birth cohort increased their parental investment levels by over .07 standard deviations, but that there was no increase among Southern whites or non-Southern African Americans. These differences are interpreted as being due to the disproportionately large increase in the rate of return to skill experienced by Southern African Americans, suggesting a strong relationship between the returns to human capital and parental behaviors.
Keywords: J01; I24; J24; J71; 330